1998
DOI: 10.1023/a:1009795330454
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Catheter ablation of the AV conduction system and permanent pacemaker implantation were associated with improved quality of life and left ventricular function in this population of highly symptomatic patients with atrial fibrillation refractory to medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 256 publications
(17 citation statements)
references
References 34 publications
1
14
1
1
Order By: Relevance
“…Our findings of improved clinical outcomes in HFrEF patients are similar to the findings in the reports of His bundle pacing in heart failure patients with or without atrial fibrillation 12, 16, 18. Previous studies demonstrated a significant improvement in echocardiographic LVEF or LV fractional shortening by 30% to 40% following AVN ablation and permanent RV pacing for refractory AF in HFrEF patients whose baseline heart rate was not controlled during AF 27, 28, 29. The mechanism of the improvement we observed was likely multifactorial and included improved heart rate control by pacing post–AVN ablation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our findings of improved clinical outcomes in HFrEF patients are similar to the findings in the reports of His bundle pacing in heart failure patients with or without atrial fibrillation 12, 16, 18. Previous studies demonstrated a significant improvement in echocardiographic LVEF or LV fractional shortening by 30% to 40% following AVN ablation and permanent RV pacing for refractory AF in HFrEF patients whose baseline heart rate was not controlled during AF 27, 28, 29. The mechanism of the improvement we observed was likely multifactorial and included improved heart rate control by pacing post–AVN ablation.…”
Section: Discussionsupporting
confidence: 87%
“…The mechanism of the improvement we observed was likely multifactorial and included improved heart rate control by pacing post–AVN ablation. The magnitude of LV function improvement in HFrEF patients in the present study appeared greater when compared to previous studies,27, 28, 29 likely due to synchronized ventricular contraction with HBP pacing post–AVN ablation. More importantly, the present study demonstrated that improvement after permanent HBP was inversely proportional to baseline ventricular function.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Ablation of a compact AV node, being currently a standard radio-frequency ablation procedure, has almost a 100% success rate, has a short duration and presents very few complications [50, 51]. Patients have permanent pacemakers implanted which are programmed to rate responsive VVI,R mode (adjusting rate according to the physiologic needs of the patient).…”
Section: Atrioventricular (Av) Node Ablation and Permanent Pacemaker mentioning
confidence: 99%
“…The APT trial [51], prospectively assessing quality of life, survival, exercise capacity and ventricular function in 156 patients within 12 months of AV node ablation for atrial fibrillation, has proved moderate improvement in left ventricular function, mostly exhibited in patients with severe left ventricular dysfunction at baseline reporting increase in LV ejection fraction from 31% to 41%. All patients demonstrated NYHA functional class improvement from 2.1 to 1.8 and noted significant improvement in quality of life.…”
Section: Atrioventricular (Av) Node Ablation and Permanent Pacemaker mentioning
confidence: 99%